Resíduos sólidos urbanos e a dimensão educativa nas escolas Crescer e Sant’Ana de Pato Branco, PR - Pinto, Carla Bordin Rocato (2023)
This research integrates the motto of discussions on Environmental Education, it is part of the Geography Education and Teaching Research Line of the Graduate Program in Geography at the State University of Western Paraná. It is developed by a member of the Education and Environmental Analysis Research Group in Southwest Paraná and a Geography teacher at the State Education Network of Paraná - SEED. It aims to understand whether the questioning of habits that generate and dispose of solid waste, from the school community, can be configured as an educational process of building new values and practices as recommended by the National Policy on Environmental Education (Law No. 9.795/1999 ) and the National Curriculum Guidelines for Environmental Education (Resolution No. 2-2012). Regarding the complexity of the origin and growth of socio-environmental problems generated by the production, consumption, and poor disposal of Urban Solid Waste (MSW), this research ponders on carrying out actions aimed at forming a sustainable community, which brings less damage. possible to the environment and lesser consequences for the community on a local scale. The research is constituted as action research, has an exploratory and descriptive character. The research subjects are 52 students from Escola Crescer and Escola Sant' Ana, both from the urban perimeter of the municipality of Pato Branco-PR; 04 workers from the municipality's recycling cooperative and 02 technicians responsible for the MSW sector of the Municipal Environment Department. The quantitative questionnaire for students, consisting of 12 questions, served as a source for obtaining initial data, while for workers at the recycling cooperative and for technicians at the Department of the Environment, we conducted an interview consisting of a script with 14 and 8 questions, respectively. The authors who are bibliographical references of the discussions carried out in the present work are: Dias (2002); Layrargues (2002); Carvalho (2004); Guimaraes (2004); Lima (2004); Sachs (2008); Gadotti (2001, 2008, 2009); Montibeller-Filho (2001); City (2001); PortoGonçalves (2004); Leff (2015); Reigota (2009), Loureiro (2012), Toffolo (2016) and Bueno (2021). Through this action-research, we understand that practical EE can be effective for teachers. We confirm that the environmental issues linked to the generation, selection and destination of USW are complex and, therefore, require an approach that indicates their causes, leaving it up to the educator to plan the approach in a continuous and progressive way, according to the age group and the ability to students' understanding. We verified that the involvement of the subjects directly involved with the MSW management and selection process enriches the educational work. The problematization of MSW selection problems in the school community, requiring the participation of students, made them more stimulated for the learning process.